Evaluation of inhibitory effect of Green Tea effervescent tablet on linoleic acid oxidation - Dadan Rohdiana; Sri Raharjo; Murdijati Gardjito (Indonesian Journal of Pharmacy, 2005)
Evaluation of the inhibitory effect of green tea effervescent tablet (TETH) on linoleic acid oxidation was carried out. TETH had the highest inhibitory effect on linoleic acid as compared with BHA, BHT, α-tocopherol and TETH-C. On tenth days incubation, TETH inhibited of linoleic acid oxidation is 50.64% followed by TETH-C, α-tocopherol, BHT and BHA as 33.83%; 33.40%; 29.51% and 26.39% respectivelly. TETH had a inhibitory effect is 1.5 times more than TETH-C and α-tocopherol or 1.7 and 1.9 times more than BHT and BHA respectivelly.Key words: inhibitory effect, green tea effervescent tablet, linoleic acid oxidation